The Impact of Technology on Labour Arbitration: Opportunities and Challenges - Ibekwe, Emmanuel Chidi; Adeyemo, Kabiru Aderemi (African Journal of Stability and Development (AJSD), 2025)
The application of technology to labour arbitration is revolutionising standard procedures, offering some benefits alongside significant challenges. This research focuses on the impact of technology, Artificial Intelligence, and remote hearings on labour arbitration. These innovations enhance efficiency and lower costs by simplifying proceedings and allowing participants to join virtually. However, they also introduce new societal issues: ethical concerns related to AI bias, security breaches of databases, and the digital divide. The use of digital tools has made arbitration more accessible to the public to some extent; however, this approach may also exclude less privileged populations due to technological gaps and limited digital literacy. By analysing materials from the ISYS database and applying theoretical frameworks such as the Diffusion of Innovations and Access to Justice, this paper discusses both the positive advancements and the challenges they pose. Remote hearings reduce common issues like case backlogs and logistical expenses, but may undermine procedural justice through reduced personal contact and difficulty in interpreting nonverbal cues. The study also questions society’s readiness for widespread digital adoption, emphasising that blind integration of digital infrastructure is unsupported without ethical standards for deploying AI and protections for personal data. Drawing on case studies and stakeholder insights, the paper offers practical guidelines to ensure that technological benefits are accessible and equitably shared, while managing potential risks. The findings underscore the significance of adaptive regulatory systems, capacity-building initiatives, and additional research into the implications of these technological shifts.